PERAN GREENPEACE DALAM MEMENGARUHI KEBIJAKAN PENGENDALIAN POLUSI UDARA DI JAKARTA (2018-2021) - Winanda, Wiwik; Saeri, Mhd. (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
This research discusses how the role of Greenpeace in influencing air pollution control policies in Jakarta during the 2018-2021 period. The annual average concentration of PM2.5 in Jakarta is often ranked in the top ten worst quality cities in the world based on reports from Air Visual. The resulting impacts of poor air quality can cause harm to the environment, health, and economic losses. The researcher uses a qualitative research method with a literature review approach. Data and information are collected and analyzed to understand the phenomenon being studied. The results of the study show that Greenpeace has been successful in influencing the air pollution control policies of the Jakarta Provincial Government through campaigns and advocacy actions, accompanied by citizen lawsuits. By presenting scientific evidence, this organization has been able to shape public opinion that supports air pollution control measures and provide valuable input for policy changes. The observed policy changes include regulations issued by the Governor, which include regulations on Strategic Zones, Air Quality Improvement, and Air Emission and Fume Discharge Management. Therefore, Greenpeace has a positive impact on shaping air pollution control policy agendas in Jakarta. This study highlights that Greenpeace tends to use the role of mobilizing public opinion and representing the voiceless. Keywords: Greenpeace, PM2.5, policy, advocacy